Misi Umat Allah (Book Review) - Martina Novalina (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
This book describes the link between biblical theology and mission. The contributors' description of biblical theology is the basis for carrying out their mission, where the mission will not be completed if it has not been translated through the implications of practical theology in a contemporary context. Contributors combine descriptions of biblical theology with contemporary contextualization. The mission of God's people is more than just biblical theology. Wright provides the reader with a complete Bible with a complete theology for a complete missionary task related to the creation, redemption, and the new creation.